COVID-19 vaccine acceptance and hesitancy among ethnic minorities in Hong Kong. Issue 5 (30th November 2022) - Chua, Gilbert T.; Lok Yan, Cheung; Wong, Wilfred HS; Sridhar, Siddharth; To, Kelvin KW; Lau, Joseph; Gurung, Sharmila; Mahtani, Shalini; Ho, Raymond; Li, Wing Sum; Yam, Jason CS; Rosa Duque, Jaime S; et al.
ABSTRACT: Ethnic minorities account for 8% of the Hong Kong population, most are Filipino and Indonesian domestic helpers taking care of children and the elderly. To understand the COVID-19 vaccination rates and factors associated with vaccine acceptance of ethnic minorities, we performed a cross-sectional questionnaire study recruiting Hong Kong ethnic minorities aged ≥18 years between 1 July and 18 July 2021 in public areas. Demographics, knowledge about COVID-19, vaccination status, intention and reasons to receive the vaccine, and planning to be re-vaccinated were analyzed. Continuous and categorical variables were compared using unpaired t-test and Chi-square test, respectively. Potential confounders were adjusted using multiple logistic regression. 2, 012 ethnic minorities participated, with a mean age of 39 years, of which 97.6% were female, 79.5% were Filipino, and 17.5% were Indonesian. 80.6% of participants were categorized as vaccine acceptance, and 69.2% were willing to be re-vaccinated. There were significantly more Filipinos than Indonesians in the vaccine acceptance group (p < .001). Subjects in the vaccine acceptance group were more likely to have higher education (p < .001), a higher COVID-19 knowledge score (p < .001), received information from the Government website (p = .003) and not from their friends or family members (p = .02), and were more confident in judging the accuracy of the information (p < .001). Logistic regression showed the mean knowledge score (β = 3.07, p < .001) and receiving information from official Government websites (adjusted OR = 1.37, p = .03) were significant factors that positively influenced vaccine acceptance. The Hong Kong Government should improve COVID-19 vaccination acceptance among ethnic minorities through public education using official channels.